Pendidikan Islam Adaptif di Era Digital: Sinergi AI Generatif dan Learning Analytics - Zaki Maulana, Muhammad (Yayasan Literasi Altruis Khatulistiwa, 2025)
The advancement of Artificial Intelligence (AI), particularly generative AI, has revolutionized global education, including Islamic education. This article aims to critically examine the integration of generative AI and learning analytics in building adaptive and data-driven Islamic learning systems. Within the context of digital education governance, these technologies offer not only administrative efficiency but also opportunities for personalized learning, enhanced digital literacy, and evidence-based decision-making. This study employs a qualitative approach through literature review and conceptual analysis of current technological trends, as well as case studies on AI implementation in several Islamic educational institutions. The findings indicate that the use of generative AI—such as Islamic chatbots, intelligent tutoring systems, and data-based mapping of students’ learning needs—can enhance learner engagement and instructional effectiveness. However, ethical concerns, infrastructure limitations, and the need for teacher training remain significant challenges. This article recommends integrative strategies that incorporate Islamic values, data security, and technological inclusivity into future Islamic education governance.